Adult Hippocampal Neurogenesis and Affective Disorders: New Neurons for Psychic Well-Being - Gomes-Leal, Walace (Frontiers in Neuroscience, 2021)
A paradigm shift in neuroscience was the discovery that new neurons are constantly produced in the adult mammalian brain of several species, including Homo sapiens. These new-born cells are formed in some main neurogenic niches, including the subventricular zone (SVZ) at the margin of the lateral ventricle and subgranular zone (SGZ) in the hippocampal dentate gyrus (DG). In the DG, neuroblasts derive from SGZ progenitors and migrate to the hippocampal granular layer becoming adult granule cells, which are integrated into functional adult circuits. It has been confirmed that adult hippocampal neurogenesis (AHN) is a long-lasting phenomenon in the human brain. The functions of hippocampal new-born cells are not fully established. Experimental studies suggest that they have unique electrophysiological properties, including hyperexcitability, which enable them to regulate adult granule cells. Their specific function depends on the anatomical hippocampal location along the hippocampal dorsal-ventral axis. Dorsal hippocampus plays a more defined role on spatial learning and contextual information, while the ventral hippocampus is more related to emotional behavior, stress resilience and social interaction. Several reports suggest a role for AHN in pattern separation, cognitive flexibility, forgetting and reversal learning. It has been proposed that deficits in AHN might impair normal DG function, including pattern separation and cognitive flexibility, which could play a role on the etiology of affective disorders, such as depression, anxiety and post-traumatic stress disorder (PTSD). In this paper, we review recent scientific evidence suggesting that impairment of AHN may underlie the pathophysiology of affective disorders even in humans and that neurogenesis-inspired therapies may be a promising approach to reduce symptoms of affective disorders in humans.